Explaining financial sustainability by rationalising the life cycle theory and permanent income theory - Siti Nur Aqilah Ab Wahab; Minah Japang; Nur Shahirah Azman (Penerbit UMS, 2024)
This article emphasizes the dynamics interaction of household financial literacy with fundamental economic consumption theories and household context of financial sustainability. The underlying concept is to explore the complexity between household financial management knowledge in the form of money attitude, behaviours and household debt motivations. By synthesizing the fundamental two household economic consumption theories, namely Life Cycle Theory and Permanent Income Theory, this article proposes an initial framework for analyzing household debt within the context of long-term personal finance sustainability body of knowledge. The integration of these two theoretical foundations allows us to nuanced examination on the multifaced factors influencing sustainable financial practices. The crucial elements in understanding household consumption patterns, debt management and repayment sustainability, money matters attitudes, investment choices that offer reasoning mental issues in managed personal finance. Finally, this article aims to provide a more comprehensive understanding on how households navigate the complexities of financial decision-making across different household lifecycles in pursuit of financial stability.